Effectiveness of home treatment in children and adolescents with psychiatric disorders - systematic review and meta-analysis - Graf, Daniel; Sigrist, Christine; Böge, Isabel; Cavelti, Marialuisa; Koenig, Julian; Kaess, Michael (BMC medicine, 2024)
Background: Home treatment in child and adolescent psychiatry offers an alternative to conventional inpatient treatment by involving the patient’s family, school, and peers more directly in therapy. Although several reviews have summarised existing home treatment programmes, evidence of their effectiveness remains limited and data synthesis is lacking. Methods: We conducted a meta-analysis on the effectiveness of home treatment compared with inpatient treatment in child and adolescent psychiatry, based on a systematic search of four databases (PubMed, CINAHL, PsychINFO, Embase). Primary outcomes were psychosocial functioning and psychopathology. Additional outcomes included treatment satisfaction, duration, costs, and readmission rates. Group differences were expressed as standardised mean differences (SMD) in change scores. We used three-level random-effects meta-analysis and meta-regression and conducted both superiority and non-inferiority testing. Results: We included 30 studies from 13 non-overlapping samples, providing data from 1795 individuals (mean age: 11.95 ± 2.33 years; 42.5% female). We found no significant differences between home and inpatient treatment for postline psychosocial functioning (SMD = 0.05 [− 0.18; 0.30], p = 0.68, I2 = 98.0%) and psychopathology (SMD = 0.10 [− 0.17; 0.37], p = 0.44, I2 = 98.3%). Similar results were observed from follow-up data and non-inferiority testing. Meta-regression showed better outcomes for patient groups with higher levels of psychopathology at baseline and favoured home treatment over inpatient treatment when only randomised controlled trials were considered. Conclusions: This meta-analysis found no evidence that home treatment is less effective than conventional inpatient treatment, highlighting its potential as an effective alternative in child and adolescent psychiatry. The generalisability of these findings is reduced by limitations in the existing literature, and further research is needed to better understand which patients benefit most from home treatment. Trial registration: Registered at PROSPERO (CRD42020177558), July 5, 2020.
Gesehen am 26.11.2024